2009
DOI: 10.1111/j.1468-0084.2008.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing Convergence in Income Distribution*

Abstract: The generalized method of moments (GMM) estimator is often used to test for convergence in income distribution in a dynamic panel set-up. We argue that though consistent, the GMM estimator utilizes the sample observations inefficiently. We propose a simple ordinary least squares (OLS) estimator with more efficient use of sample information. Our Monte Carlo study shows that the GMM estimator can be very imprecise and severely biased in finite samples. In contrast, the OLS estimator overcomes these shortcomings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…Thus, the preliminary results lend very weak support, if any, to the convergence in income inequality by using the 'top1' indicator. This may not appear too surprising as Bao and Dhongde [1] have shown that the GMM estimates can be severely biased in finite samples and the associated variances (or standard errors) can be very imprecise as well. This is particularly true in our application where there are only 48 states (N = 48).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Thus, the preliminary results lend very weak support, if any, to the convergence in income inequality by using the 'top1' indicator. This may not appear too surprising as Bao and Dhongde [1] have shown that the GMM estimates can be severely biased in finite samples and the associated variances (or standard errors) can be very imprecise as well. This is particularly true in our application where there are only 48 states (N = 48).…”
Section: Resultsmentioning
confidence: 89%
“…As such, Bao and Dhongde [1] propose to estimate the parameters by using an OLS procedure based on the following first-differenced model…”
Section: Empirical Strategymentioning
confidence: 99%
See 3 more Smart Citations